(untitled) (Journal of Management and Social Sciences, 2021)
Abstract Despite the fact that Nigeria was colonized by Britain and inherited local government administrative structure from her former colonial rulers, there are lots of differences in the establishment, structure, composition, finance, functions, pattern and efficiency in local government administration in both countries. Therefore, the objective of this paper is to examine the differences in Nigerian Local Government System with/to that of Britain. The study adopted democratic participatory theory as the basis of the argument and relied on documentary method for its analysis. The paper finds that local government in Nigeria has been subjected to the control of both state and federal governments and other challenges such as poor service delivery and corruption among others. It was thus recommended that Nigerian Government must emulate her former colonial ruler (Britain) and respect the provisions in the constitution that grants autonomy to local governments as a third tier of government and seek ways to ensure transparency, accountability and make provision for democratically elected Local Government Councils as this will lead to the development of the Local Councils. Keywords Local government, local administration, democratic participation, constitution, service delivery